Memperkenalkan Peran Merek Di Suatu Produk Kepada Masyarakat Gampong Tanjung Selamat - Cacak Rinunate; Salsabila Hajian; Taufiq C. Dawood (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This community service program activity has the theme "Introducing the role of a product brand to the people of Gampong Tanjung Selamat". The main activity is to introduce the role of a product brand to the Tanjung Selamat village community. The aim of this activity is to provide appropriate education regarding the introduction of the role of a product brand to consumers and increase brand awareness that a product brand has an important role in influencing society. This activity collaborates with Aceh's micro, small and medium enterprises by holding community outreach with Aceh's micro, small and medium enterprises, using the lecture learning method accompanied by open interactive sessions for participants. The results obtained from this activity are that there is better knowledge regarding the importance of a product brand to consumers in the community in Gampong Tanjung Selamat so that it becomes the basic capital for the community to start and realize the importance of the role of brands.